Research on Factors Affecting the Disclosure of Sustainable Development Report: Experimental at Vietnam National Petroleum Group - Tuan, Le Anh; Hai, Phan Thanh; Hung, Nguyen Xuan; Nhi, Vo Van (Asian Economic and Financial Review, 2019)
This research analysed with data from 265 managers from head level upwards working in 60 oil trading companies in the Vietnam National Petroleum Group (Petrolimex) spread across the country to examine factors affecting the disclosure of sustainable development reports. The following methods of descriptive statistics, Cronbach’s Alpha, Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) are employed in this study. The empirical results show that enterprise size, growth opportunities, legal basis, business sector and profitability are factors that have a varying positive impact on disclosing sustainable development reports. The managerial viewpoint, though influencing the impact, is not statistically significant for disclosing sustainability development reports. The results provide a scientific basis for managers to make appropriate decisions in improving the disclosure of sustainable development reporting information.